In Vitro Modulation of Human Intestinal Microbiota by Mannoligosaccharides Synthesized from Amorphophallus muelleri Glucomannan - ACHMAD DINOTO; CORY CORAZON WATUMLAWAR; YOPI YOPI (Indonesian Society for microbiology, 2013)
The corms of Amorphophallus muelleri Blume contain a large amount of glucomannan, a kind of polysaccharide that are commonly consumed by people as gelly foods. In order to improve the beneficial properties of glucomannan, we previously have established the enzymatic process to produce the mannoligosaccharides from flour of glucomannan using microbial mannanase. The effects of mannoligosaccharides on the growth modulation of human intestinal microbiota were investigated in this study. A set of in vitro single batch culture experiment was conducted to study the effect of mannooligosaccharides on human-origin Lactobacillus fermentum AA0014 and Lactobacillus plantarum FU0811. A modified MRS medium containing 10% (w/v) sucrose, glucomannan, and mannoligosaccharide was used instead of glucose as carbon source. The results showed the highest growth rate (0.13 h-1) with both L. fermentum AA0014 and L. plantarum FU0811 in the presence of mannooligosaccharides. We confirmed this result by a similar in vitro experiment using human fecal samples of six healthy adults as innocula and analyzed the microbial population by fluorescence in situ hybridization (FISH). Lactobacilli were proliferated higher in the presence of mannoligosaccharide than other carbon sources, yielding the microbial proportion as much of 10.9% of total microbiota. Overall, this study demonstrated the potential use of mannoligosaccharides synthesized from A. muelleri glucomannan as prebiotic candidate of modulating the beneficial human intestinal microbiota.